Exploring the Community Structure of Plankton in the Maricultures Sites of Kodek Bay, Lombok Island - Widiastuti Widiastuti; Sheliya Desmita Br. Bangun; Ni Luh Yustika Giri; Varian Fahmi (Universitas Diponegoro, 2023)
Mariculture is considered a future economic source for Indonesia. However, this practice may degrade the surrounding ecosystem by decreasing the water quality, including the plankton community. This study aimed to determine the community structure of plankton (phytoplankton and zooplankton) in the mariculture sites. Study sites were selected based on the mariculture activities of the Research Center for Marine and Terrestrial Bioindustry (PRBILD-BRIN) located in Kodek Bay, Lombok Island. Samplings were conducted in February 2021, zooplankton samples were collected horizontally by towing a 100 Î¼m plankton net using a boat, whereas phytoplankton was collected using a 20 Î¼m plankton net horizontally. The plankton samples were preserved with 4% formaldehyde, identified, and counted in a Sedgwick Rafter cell counter using an Olympus CX21 (10x). Results demonstrated that zooplankton was dominated by genera from the Subclass Copepoda (Temora sp., Microsetella sp., Euterpina sp., Oithona sp., Acartia sp., and Onceae sp.) that were significantly more abundant at Sites 1 and 2 than those at Sites 3 and 4. The diversity levels were moderate at all sites, except at site 1, which Temora dominated. Phytoplankton was mainly composed of Bacillariophyceae, followed by Dinophyceae, Chlorophyceae, and Conjugatophyceae, with no significant difference in abundance at all sites. The diversity levels were low for all phytoplankton taxa at all sites except at site 2, where Bacillariophyceae and Dinophyceae equally composed the community. It is suggested that the mariculture organisms may shape these phytoplankton and zooplankton community structures by recycling particular nutrients.Â